2009
DOI: 10.1002/rcm.4374
|View full text |Cite
|
Sign up to set email alerts
|

Non‐disturbing characterization of natural organic matter (NOM) contained in clay rock pore water by mass spectrometry using electrospray and atmospheric pressure chemical ionization modes

Abstract: We have investigated the composition of the mobile natural organic matter (NOM) present in Callovo-Oxfodian pore water using electrospray ionization mass spectrometry (ESI-MS), atmospheric pressure chemical ionization mass spectrometry (APCI-MS) and emission-excitation matrix (EEM) spectroscopy. The generation of knowledge of the composition, structure and size of mobile NOM is necessary if one wants to understand the interactions of these compounds with heavy metals/radionuclides, in the context of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…182 However, in accepting the resolving power of MS detection, one has to also acknowledge potential biases originating from the ionisation source, which can be more efficient for certain classes of compounds over others, and the additional risk of insource fragmentation. 39,187,188 2.1.3. Singly or multiply charged ions can be generated, and the number of charges retained by a particular analyte depends on factors such as molecular size, chemical composition, the solvent composition and the instrument parameters.…”
Section: Reversed-phase Liquid Chromatographymentioning
confidence: 99%
“…182 However, in accepting the resolving power of MS detection, one has to also acknowledge potential biases originating from the ionisation source, which can be more efficient for certain classes of compounds over others, and the additional risk of insource fragmentation. 39,187,188 2.1.3. Singly or multiply charged ions can be generated, and the number of charges retained by a particular analyte depends on factors such as molecular size, chemical composition, the solvent composition and the instrument parameters.…”
Section: Reversed-phase Liquid Chromatographymentioning
confidence: 99%
“…The immobile organic matter which is present in about 1000 times larger quantity did not become remobilized over the experimental time frame. The principal compound types observed in DOM (Huclier-Markai et al, 2010) were acidic compounds, fatty acids, aldehydes, amino acids, and lower aging humic compounds, suberic and tiglic acid being a typical of the observed molecules. Organic matter is known to decrease the retention of radionuclides on clay and to increase mobility.…”
Section: Resultsmentioning
confidence: 98%
“…The chemical composition of NOM contained in the clay‐rich rock pore water was determined under in situ like conditions by electrospray ionization mass spectrometry (ESI‐MS) and atmospheric pressure chemical ionization MS. These techniques have shown their efficiency in resolving natural DOM molecular complexity into discrete components, notably for DOM contained in COx pore water extracted from boreholes . DOM can range in molecular weight from a few hundred to 100 000 Da, which is in the colloidal size range.…”
Section: Introductionmentioning
confidence: 99%
“…DOM can range in molecular weight from a few hundred to 100 000 Da, which is in the colloidal size range. But, the majority of molecules were identified as being of low molecular weight and it was observed that they were mainly acidic compounds, fatty acids, as well as aldehydes and amino acids . Due to the low concentrations of fulvic and humic acids in the COx, the inventory was focused on the smallest organic molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation